Using stories to facilitate the development of metacognitive awareness of young learners in the Intermediate Phase - Van Aswegen, Suzanne Laetitia (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2016.